SURVEI METODE PENGUKURAN APLIKASI CHATBOT BERBASIS MEDIA SOSIAL - Ratna Ayu Sekarwati; Ahmad Sururi; Rakhmat Rakhmat; Miftahul Arifin; Arief Wibowo (Gema Teknologi, 2021)
The design of Chatbot aims to facilitate social activities in all areas to be considered. Chatbot is one type of machine that can communicate with humans using natural language. Communication happening via chat is a written conversation. Chatbot is a form of application implementation from Natural Language Processing (NLP) that belongs to one branch of artificial intelligence or Artificial Intelligent (AI). Social Media now provides a service that allows developers to process and integrate chatbot applications. This paper aims to review the papers that build chatbot applications in various social media using various testing methods. The contribution of this paper is to determine which method is able to measure the level of chatbot accuracy well. This review paper will choose the equation of the most widely used test methods and social media from various papers so that further research is expected to implement the right testing methods and use better social media in terms of user experience, features, and services. The review paper shows that the Black-box and System Usability Scale testing methods are most used in the review paper. This testing method is a type of method that performs testing of the flow and how the chatbot works to achieve functional validation throughly.